Challenges In Teaching Foreign Languages Using Modern Innovative Pedagogical Technologies (Zien Journal of Social Sciences and Humanities, 2025)
This article explores the challenges and opportunities associated with teaching foreign languages through the use of innovative pedagogical technologies. It discusses the evolution of technological tools in language education, ranging from multimedia resources to cutting-edge technologies such as artificial intelligence, virtual reality, and augmented reality